Psychological Fluency and Its Relationship with Creative Teaching Practices among Physical Education Instructors in Light of Gender and Educational Environment Variables (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study addresses the variability in psychological fluency and creative teaching practices observed among physical education teachers across different schools and regions. The discrepancy may stem from individual differences, demographic factors such as gender, and environmental contexts, including urban and rural educational settings. The objectives of the study were to assess the level of psychological fluency and creative teaching practices among physical education teachers in relation to gender and educational environment, and to examine the correlation between these two variables. A descriptive survey and correlational design were employed. The research population comprised 759 physical education teachers in Dhi Qar Governorate, divided by gender (376 male and 383 female) and by educational environment (310 in rural schools and 449 in central schools). From this population, a total sample of 540 teachers was selected and further distributed into exploratory, construction, and application groups. The findings revealed a strong positive correlation between psychological fluency and creative teaching practices, suggesting that teachers with higher psychological fluency are more likely to employ creative teaching strategies. Furthermore, gender and educational environment were found to be relevant factors in shaping these practices. In conclusion, psychological fluency serves as a significant predictor of creative teaching practices. Enhancing psychological fluency among physical education teachers may therefore contribute to improving the quality and creativity of their instructional performance.